2020
DOI: 10.56053/4.2.115
|View full text |Cite
|
Sign up to set email alerts
|

ZnO-based sensors with controlled ethanol sensing

Abstract: ZnO microcrystals are synthesized through a facile solution method and characterized by field-emission scanning electron microscopy, transmission electron microscopy, selected area electron diffraction and X-ray diffraction. The ethanol sensing properties of these microcrystals are investigated by spin-coating them on a silicon substrate with Pt electrodes to fabricate a micro-structure sensor. The sensitivity is up to 8 when the sensor is exposed to 50 ppm ethanol, and the response time and recovery time are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…Both types of catalyst execute asymmetric addition of cyclohexanone 137 with N-PMP-benzaldimine 138 to afford corresponding bridged compounds 139a−139c with expected enantioselectivity. 35 The solvent optimization study reported that nonpolar aprotic solvents toluene and m-xylene led to higher yields than their polar counterparts like halogenated solvents. The phosphoric acid 141-catalyzed direct aza Diels− Alder reaction was extended to a series of benzaldimines (138), with an electron donating or electron withdrawing substituent afforded endoisomer 139 in 70−82% yield and with up to 87% enantioselectivities.…”
Section: Applications Of H 8 −Binol Moleculementioning
confidence: 99%
“…Both types of catalyst execute asymmetric addition of cyclohexanone 137 with N-PMP-benzaldimine 138 to afford corresponding bridged compounds 139a−139c with expected enantioselectivity. 35 The solvent optimization study reported that nonpolar aprotic solvents toluene and m-xylene led to higher yields than their polar counterparts like halogenated solvents. The phosphoric acid 141-catalyzed direct aza Diels− Alder reaction was extended to a series of benzaldimines (138), with an electron donating or electron withdrawing substituent afforded endoisomer 139 in 70−82% yield and with up to 87% enantioselectivities.…”
Section: Applications Of H 8 −Binol Moleculementioning
confidence: 99%
“…When tested, the prelithiated MXene demonstrated a higher specific capacity and reduced Li + ions during SEI formation. Figure 8(a) shows the schematic of the working conditions of the MXenes before and after prelithiation, demonstrating that prelithiation can increase the MXene interlayers and recompense the Li loss in the initial cycle leading to a high reversible capacity [97]. Another study by Naguib et al revealed that upon mixing of V 2 CT x with-TBAOH for two hours, a peak shift from 2θ of 8.9°to 4.6°(c-LP from 19.9 Å to 38.6 Å) was observed.…”
Section: Effect Of Interlayer Spacing and Functionalization Of Vanadi...mentioning
confidence: 99%
“…The high resolution V 2p spectrum can be deconvoluted into four components corresponding to V 5+ , V 4+ , V 3+ and V 2+ /V-C, respectively. The peaks of V 3+ are attributed to the loss of V during HF etching [43]. The C 1s spectrum can be deconvoluted into six components corresponding to C-V, C-C, C-O, C=O, O-C-O and -COOH, respectively.…”
Section: Microstructurementioning
confidence: 99%